Karakteristik Pengujian Tegangan Tembus Arus Bolak Balik (AC) Pada Minyak RBDPO Olein Sebagai Alternatif Isolasi cair - Meliana Meliana; Fri Murdiya (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Transformer Oil that mostly comes from Mineral Oil (MO) is originated from fossil fuel that is harmful to the environment, do not biodegrade easily, it is a non-renewable resourceand it requires time to extract. Hence, an oily liquid isolation is needed which derives of vegetable oil,one of the examples; extracted of Palmoil that is already processed into RBDPO Olein. This research aim is to test the characteristic of AC Breakdown Voltage on RBDPO Oleinas a liquid isolation alternative and transformer oil as a comparison. The breakdown voltage of RBDPO Olein oil is more important than mineral oil. This research also examines the effect of temperature increase variation on isolation oil, electrode distance variation, variation of the electrode utilized, and effect of the decrease of oil water ratio of RBDPO Olein towards isolation oil breakdown voltage. A higher temperature of the isolation oil, a wider electrode distance, and reduction of oil water ratio on isolation oil shall generate a higher breakdown voltage. For the variation of using partial ball electrode and ball electrode from the same material, it generates an almost similar breakdown voltage. As an alternative liquid isolation, the RBDPO Olein oil has fulfilled several criteria as per liquid isolation specification which include breakdown voltage, the effect of temperature variation on breakdown voltage, oil clearance, density, viscosity. However, the pour point and flash point have not fulfilled the criteria as a liquid isolation alternative.Keywords: RBDPO Olein, Breakdown Voltage, Partial Ball Electrode, Balls Electrode, Liquid Isolation.